2000
DOI: 10.1287/orsc.11.3.263.12503
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Act: Learning from Organizing Practices in Cultural Industries

Abstract: The dilemmas experienced by managers in cultural industries are also to be found in a growing number of other industries where knowledge and creativity are key to sustaining competitive advantage. Firms that compete in cultural industries must deal with a combination of ambiguity and dynamism, both of which are intrinsic to goods that serve an aesthetic or expressive rather than a utilitarian purpose. Managers involved with the creation, production, marketing, and distribution of cultural goods must navigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
372
0
28

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 450 publications
(405 citation statements)
references
References 8 publications
5
372
0
28
Order By: Relevance
“…Like many other cultural fields, the video game industry is one that rewards novelty, especially when it is packaged in terms that are recognizable to consumers and critics (Lampel et al 2000;Hutter 2011). Doubtless, some video games are little more than simple imitations of already existing games.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Like many other cultural fields, the video game industry is one that rewards novelty, especially when it is packaged in terms that are recognizable to consumers and critics (Lampel et al 2000;Hutter 2011). Doubtless, some video games are little more than simple imitations of already existing games.…”
Section: Datamentioning
confidence: 99%
“…In striving for novelty, a creative team risks producing a product that cannot be assimilated to the tastes of critics and consumers. Whether wide or razor thin, the difference between "exciting" and "weird" can be the difference between a hit and a flop (DiMaggio 1997;Lampel, Lant, and Shamsie 2000;Hutter 2011). Novelty is neither sufficient nor necessary for success-for sometimes consumers and critics reward conformity.…”
mentioning
confidence: 99%
“…Their creative thinking and planning abilities play an important role in that process. Directors have to select and recombine various professionals in order to satisfy external demands for novelty in the final product as well as their own needs for creative renewal (Lampel, Lant, & Shamsie, 2000;Menger 1999). Lampel and Shamsie (2003) found that the success of films in the US film industry is directly related to the mobilization and transformation of talent.…”
Section: Cinematic Theatrical and Television Directorsmentioning
confidence: 99%
“…Cultural-creative products and services elude mechanistic and systematic evaluation (Caves, 2000;Lampel et al 2000) and call for a complex mixture of formalized knowledge, informal reference, experience, taste and personal judgment because 'markets of singularities could not function' without evaluation by experts (Karpik, 2010, p.46). Evaluation and evaluative practices have over the years received attention from social science scholars in general and in particular in the fields of education and research (e.g.…”
Section: Research Opportunities and Implicationsmentioning
confidence: 99%